Morphological and functional characteristics of chilled semen obtained from domestic feline epididymides (Felis catus) - Balbin Villaverde, A. I. Silva; Martins, M. I. Mello; Castro, V. Basto; Lopes, Maria Denise [UNESP] (Elsevier B.V., 2006)
The objective of this study was to determine morphological and functional characteristics of semen retrieved from the feline epididymis before and after cooling. Sixteen adult male cats were orchiectomized. The distal portion of the epididymis and proximal part of the deferent ducts were dissected and squeezed to obtain their content. After centrifugation, the supernatant was removed, sperm were resuspended in a 0.9 mL Tris-fructose-citric acid extender containing 20% egg yolk, aliquoted into three 0.3 mL samples, placed in a refrigerator (4.8 degrees C) and cooled (0.5 degrees C/min). Semen evaluations were performed on four occassions: immediately after epididymal sperm retrieval (TO), and at 24 h (T-1), 48 h (T-2) and 72 h (T-3) after cooling. on each occasion, progressive motility, vigor and sperm morphology were determined. Mean motility and vigor decreased (P < 0.05) between each successive examination. Although the majority of sperm cell damage occurred within the first 24 h, there was a decrease (P < 0.05) in mean percentage of morphologically normal sperm between To and each evaluated time (T-1, T-2, T-3) after cooling, due to an increase in coiled and bent sperm tails. Further studies are needed to evaluate the effects of cooling on the fertilizing capacity of cat epididymal spermatozoa in assisted reproduction programs. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: epididymal spermatozoa; semen cooling; cat; feline